2(2x+3)=-x+1

Simple and best practice solution for 2(2x+3)=-x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+3)=-x+1 equation:


Simplifying
2(2x + 3) = -1x + 1

Reorder the terms:
2(3 + 2x) = -1x + 1
(3 * 2 + 2x * 2) = -1x + 1
(6 + 4x) = -1x + 1

Reorder the terms:
6 + 4x = 1 + -1x

Solving
6 + 4x = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
6 + 4x + x = 1 + -1x + x

Combine like terms: 4x + x = 5x
6 + 5x = 1 + -1x + x

Combine like terms: -1x + x = 0
6 + 5x = 1 + 0
6 + 5x = 1

Add '-6' to each side of the equation.
6 + -6 + 5x = 1 + -6

Combine like terms: 6 + -6 = 0
0 + 5x = 1 + -6
5x = 1 + -6

Combine like terms: 1 + -6 = -5
5x = -5

Divide each side by '5'.
x = -1

Simplifying
x = -1

See similar equations:

| -9x-19=-5x-43 | | -4=2(5x+3)+10 | | 3x+13=-6x+121 | | -18=3(x+2)+3 | | 10x+18=158 | | 2(5x+2)+1=-5 | | -21=3(4x+5) | | 5(3x+4)=5x+10 | | -35=5(3x-1) | | 2e-8f+6e+3f= | | 25=5(2x-5) | | 5(2x-5)=25 | | 3(5x-5)-9=36 | | 4(2x-5)+6=-46 | | 3(3x+2)=3x-36 | | -12=3(x+5) | | 3b-4a-(2b+a)= | | 5x+26=5(5x-3)+1 | | 6(1-2x)-3(x+1)= | | -x-6=7x-62 | | 7h-26=23 | | 4(2x+2)=-x-10 | | 4x+1=3(x-5)+5 | | 4=4(x+4) | | -5x-7=-3x-33 | | 4(x-5)=-2x-2 | | -x+28=-4x+49 | | -11x+34=-5x+64 | | 2(x+4)+9=29 | | 22=3(3x+3)+4 | | -2x-1=5(4x+5)-4 | | x+34=5(x+1)-3 |

Equations solver categories